Wind tunnel tests of the dynamic processes that control wind erosion of a sand bed. Issue 2 (29th November 2018) - Wang, Xuesong; Zhang, Chunlai; Huang, Xiaoqi; Shen, Yaping; Zou, Xueyong; Li, Jiao; Cen, Songbo
Abstract: Aeolian sand transport is a complicated process that is affected by many factors (e.g. wind velocity, sand particle size, surface microtopography). Under different experimental conditions, erosion processes will therefore produce different results. In this study, we conducted a series of wind tunnel experiments across a range of wind velocities capable of entraining sand particles (8.0, 10.0, 12.0, and 14.0 m s ‐1 ) to study the dynamic changes of the shear velocity, aerodynamic roughness length, and sand transport. We found that the shear velocity and aerodynamic roughness length are not constant; rather, they change dynamically over time, and the rules that describe their changes depend on the free‐stream air velocity. For wind tunnel experiments without feeding sand into the airflow, the sand bed elevation decreases with increasing erosion time, and this change significantly affected the values of shear velocity and aerodynamic roughness length. A Gaussian distribution function described the relationships between the sand transport rate ( q T ) and the duration of wind erosion ( T ). It is therefore necessary for modelers to consider both deflation of the bed and the time scale used when calculating sand transport or erosion rates. © 2018 John Wiley & Sons, Ltd. Abstract : The dynamic changes of various wind erosion factors and the response of soil wind erosion rate to the change of the factors was observed in a wind tunnel. Wind is the cause of sand flow, while the sand flow can affect the wind in turn.